Performance indicators contributing to success at the group and play-off stages of the 2019 Rugby World Cup - Bunker, R.; Spencer, K. (Journal of Human Sport & Exercise, 2022)
The performance indicators that contributed to success at the group and play-off stages of the 2019 Rugby World Cup were investigated using publically available data obtained from the offcial tournament website. Ball carry effectiveness—as measured by the percentage of ball carries that penetrated the opposition gainline, and total meters gained—as measured by kick meters plus carry meters, were found to contribute to success at both stages of the tournament. However, while dominating possession, carrying the ball more frequently, making more passes, winning more rucks, and making less tackles contributed to success at the group stage of the tournament, the opposite was true at the play-off stage. The obtained results reiterate the need for teams to adjust their playing strategies at the play-off stage of the tournament.